Overview of the rectangular wire windings AC electrical machine - Zhao, Yu; Li, Dawei; Pei, Tonghao; Qu, Ronghai (CES Transactions on Electrical Machines and Systems, 2019)
The rectangular wire winding AC electrical machine has drawn extensive attention due to their high slot fill factor, good heat dissipation, strong rigidity and short end-windings, which can be potential candidates for some traction application so as to enhance torque density, improve efficiency, decrease vibration and weaken noise, etc. In this paper, based on the complex process craft and the electromagnetic performance, a comprehensive and systematical overview on the rectangular wire windings AC electrical machine is introduced. According to the process craft, the different type of the rectangular wire windings, the different inserting direction of the rectangular wire windings and the insulation structure have been compared and analyzed. Furthermore, the detailed rectangular wire windings connection is researched and the general design guideline has been concluded. Especially, the performance of rectangular wire windings AC machine has been presented, with emphasis on the measure of improving the bigger AC copper losses at the high speed condition due to the distinguished proximity and skin effects. Finally, the future trend of the rectangular wire windings AC electrical machine is prospected.